Money, Death, and Agency in Catholic Ireland, 1850–1921. Issue 3 (25th November 2019) - Doyle, Patrick; Roddy, Sarah
Abstract: Between the end of the Great Famine and the end of the union with Britain, the Irish Catholic Church was almost exclusively funded by ordinary lay people. This article examines the financial relationship between clergy and laity, focusing on payments related to death. In doing so, it argues three main points. First, it suggests that previous conceptions of lay people coerced into giving their money to the church are too simplistic and deny the complex agency of the people of many social classes who gave the money. Second, it argues that using the financial transactions of ordinary people gives historians a much-needed methodology for recovering lives about which the archives are otherwise silent. Third, it posits that the mediation of faith through money, specifically, must be added to the growing body of work on "material religion."